2018
DOI: 10.1177/0300985818780449
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Colitis in Rhesus Macaques Is Associated With Dysbiosis, Abundant Enterochromaffin Cells and Altered T-Cell Cytokine Expression

Abstract: Idiopathic chronic diarrhea (ICD) is a common ailment affecting captive rhesus macaques ( Macaca mulatta). ICD cases are characterized by diarrhea in the absence of commonly identified diarrheal pathogens and multiple recurrences even after supportive therapy. Histologically, the disease is characterized by lymphoplasmacytic colitis. We identified 35 rhesus macaques euthanized for ICD during a 7-month period and described demographic, clinical, histologic, and immunologic commonalities. We found a trend of his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 49 publications
5
56
0
Order By: Relevance
“…Alternatively, these Helicobacter species could be more susceptible to antibiotics than Campylobacter resulting in its depletion. Indeed, a recent study using rhesus macaques reported a large decrease in Helicobacter following vancomycin treatment despite the observation that Helicobacter should not be directly susceptible to vancomycin [87, 88].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, these Helicobacter species could be more susceptible to antibiotics than Campylobacter resulting in its depletion. Indeed, a recent study using rhesus macaques reported a large decrease in Helicobacter following vancomycin treatment despite the observation that Helicobacter should not be directly susceptible to vancomycin [87, 88].…”
Section: Discussionmentioning
confidence: 99%
“…P . hominis has been associated with chronic diarrhoea and/or inflammatory bowel disease in animals [56], nonhuman primates [57] and humans [58], and is found in 14% of pregnant women in Papua New Guinea. In our study affected VL cases had higher abundance of P .…”
Section: Discussionmentioning
confidence: 99%
“…40 Increased abundance of Helicobacter brantae was shown in a batch of commercially hatched broiler parent chickens (over 80% of ileal microbiota in individual chickens). 40 Increased abundance of Helicobacter brantae was shown in a batch of commercially hatched broiler parent chickens (over 80% of ileal microbiota in individual chickens).…”
Section: Pre S En Ce Of Non -H Elicobac Ter Pylori Helicobac Ter S mentioning
confidence: 99%
“…On the other hand, the analysis of 35 rhesus macaques euthanized for ICD demonstrated that ICD was associated with dysbiosis involving Campylobacter and Trichomonas, and a loss of Helicobacter macacae. 40 Increased abundance of Helicobacter brantae was shown in a batch of commercially hatched broiler parent chickens (over 80% of ileal microbiota in individual chickens). 41 Eimeria parasite coccidiosis is an economically important disease of poultry and livestock worldwide.…”
Section: Pre S En Ce Of Non -H Elicobac Ter Pylori Helicobac Ter S mentioning
confidence: 99%